Symptoms of cybersex addiction can be linked to both approaching and avoiding pornographic stimuli: results from an analog sample of regular cybersex users - Snagowski, Jan; Brand, Matthias (Frontiers in Psychology, 2015)
The phenomenology, classification, and diagnostic criteria of cybersex addiction are discussed controversial. Some approaches point towards similarities to substance dependencies for which approach/avoidance tendencies are crucial mechanisms. Several researchers have argued that within an addiction-related decision situation, individuals might either show tendencies to approach or avoid addiction-related stimuli. In the current study 123 heterosexual males completed an Approach-Avoidance-Task (AAT; Rinck & Becker, 2007) modified with pornographic pictures. During the AAT participants either had to push pornographic stimuli away or pull them towards themselves with a joystick. Sensitivity towards sexual excitation, problematic sexual behavior, and tendencies towards cybersex addiction were assessed with questionnaires. Results showed that individuals with tendencies towards cybersex addiction tended to either approach or avoid pornographic stimuli. Additionally, moderated regression analyses revealed that individuals with high sexual excitation and problematic sexual behavior who showed high approach/avoidance tendencies, reported higher symptoms of cybersex addiction. Analogous to substance dependencies, results suggest that both approach and avoidance tendencies might play a role in cybersex addiction. Moreover, an interaction with sensitivity towards sexual excitation and problematic sexual behavior could have an accumulating effect on the severity of subjective complaints in everyday life due to cybersex use. The findings provide further empirical evidence for similarities between cybersex addiction and substance dependencies. Such similarities could be retraced to a comparable neural processing of cybersex- and drug-related cues.